Manufacture of cylinders with axial imperfections - Khirotdin, Khairilhijra (2004)
The report outlines the methodology and procedures used to manufacture the thin walled cylinder with its axial imperfections using a NUM 1060 CNC Lathe machine. By introducing the known geometries imperfections, the thin cylinder manufactured could be analyzed under different load conditions and with different type of applications. The cylinders manufactured were to have minimum thickness set up with their flat end were machined to follow a periodic sinusoidal wave's function of specified amplitude and frequency. In addition, the flat end cylinder circumference surface was also required to have a constant chamfer angle either from the outside or inside cylinder surface. A number of experiments were attempted to determine the minimum thickness, the sinusoidal wave's function and the constant chamfer angles required. At the end of the project, the machining techniques and procedures used to manufacture the cylinder were successfully established as well as the CNC part programs which played a major role in producing the imperfections required. A result of a satisfactory final thin cylinder was manufactured even though some difficulties had occurred throughout the whole project. Finally, all the information contained were vital for understanding the concept of manufacturing the cylinders with axial imperfections. It indicates some essential findings for the clear description of the project purposes and the necessary works that undertaken through the completion of the project.